The impact of Codonopsis Pilosulae and Astragalus Membranaceus extract on growth performance, immunity function, antioxidant capacity and intestinal development of weaned piglets - Guo, Rongxia; Zhang, Hao; Jiang, Chenghui; Niu, Chun; Chen, Baoxia; Yuan, Ziwen; Wei, Yanming; Hua, Yongli (Frontiers in Veterinary Science, 2024)
IntroductionThe objective of this study was to examine the impact of Codonopsis pilosula and Astragalus membranaceus extract (CA) on the growth performance, diarrhea rate, immune function, antioxidant capacity, gut microbiota, and short-chain fatty acids (SCFAs) in weaned piglets.MethodsA total of forty-eight 31-day-old weaned piglets, were divided into four groups randomly based on the treatment type: control group (CON), low dose group (LCA, 0.5% CA), medium dose group (MCA, 1.0% CA), and high dose group (HCA, 1.5% CA), and were fed for a duration of 28 days. On the morning of the 1st and 29th day, the piglets were assessed by weighing them on an empty stomach, recording their daily feed intake and diarrhea rate.ResultsCA increased the average daily weight gain and reduced F/G without significant differences, and the diarrhea rate was reduced in the LCA and MCA groups. Furthermore, the levels of T-AOC, SOD, GSH-Px, and MDA were increased. The levels of T-AOC in the LCA group and the MCA group, SOD in the MCA group, and GSH-Px in the HCA group were significantly higher compared with the CON group (p < 0.05). Additionally, CA significantly increased IgM, IgG, and IgA levels (p < 0.05). The results of gut microbiota analysis showed that the bacterial population and diversity of faeces were changed with the addition of CA to basal diets. CA increased the abundance of the beneficial bacterial Firmicutes and Lactobacillus. Additionally, Compared with the CON group, CA significantly increased the SCFAs content of weaned piglets (p < 0.05).DiscussionCA can alleviate oxidative stress, improve immunity and antioxidant capacity, increase the abundance of beneficial bacteria, and the content of SCFAs for improving the intestinal barrier of piglets, thus promoting growth and reducing diarrhea rate in weaned piglets.